2019
DOI: 10.1007/s10803-019-04156-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Use of Cognitive–Behavioral Therapy with Autistic Adults: A Survey of Community Mental Health Clinicians

Abstract: Cognitive-behavioral therapy (CBT) can improve anxiety and depression in autistic adults, but few autistic adults receive this treatment. We examined factors that may influence clinicians' use of CBT with autistic adults. One hundred clinicians completed an online survey. Clinicians reported stronger intentions (p = .001), more favorable attitudes (p < .001), greater normative pressure (p < .001), and higher self-efficacy (p < .001) to start CBT with non-autistic adults than with autistic adults. The only sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 25 publications
4
50
1
Order By: Relevance
“…Although these findings were drawn from a specific EBP implementation effort within one large county in California, the recommendations for tailored ASD policy regarding service delivery parameters and workforce training in short-term evidence-based interventions to address co-occurring MH needs are likely generalizable to other service systems (e.g. community MH services for adults with ASD) that are planning or actively engaged in formal EBP implementation (Maddox et al, 2019; Maddox & Gaus, 2019). They may also be relevant to other clinically complex groups, such as youth with co-occurring MH and substance use conditions, who may also not be the primary target of PEI but likely still utilize and could benefit from these services.…”
Section: Discussionmentioning
confidence: 99%
“…Although these findings were drawn from a specific EBP implementation effort within one large county in California, the recommendations for tailored ASD policy regarding service delivery parameters and workforce training in short-term evidence-based interventions to address co-occurring MH needs are likely generalizable to other service systems (e.g. community MH services for adults with ASD) that are planning or actively engaged in formal EBP implementation (Maddox et al, 2019; Maddox & Gaus, 2019). They may also be relevant to other clinically complex groups, such as youth with co-occurring MH and substance use conditions, who may also not be the primary target of PEI but likely still utilize and could benefit from these services.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, for those on the autism spectrum, treatment strategies to facilitate the individuals' communication of mood, feelings, and experiences may also be helpful to make sure they feel they are being heard and validated. Furthermore, identifying strategies to help professionals understand, identify, and treat depression in autism earlier and better should be a focus of future research and training efforts (Maddox et al, 2019(Maddox et al, , 2020. Unfortunately, treatments for depression in autism, especially among adults, have shown limited effectiveness (Chandrasekhar & Sikich, 2015;Kiep et al, 2015;Lake et al, 2014;Sizoo & Kuiper, 2017;Spain et al, 2015;K.…”
Section: Themesmentioning
confidence: 99%
“…Mental health providers' low self-confidence and efficacy to work with autistic clients is a significant limitation to service availability; clinicians report more favorable attitudes, greater normative pressure, and higher self-efficacy to provide CBT to non-autistic clients (Maddox, Crabbe, Fishman, et al, 2019). In their survey of 100 community mental health therapists, Brookman-Frazee and colleagues found that although 76% of providers reported having seen an autistic child, therapists perceived working with autistic children as a significant challenge for which they had not been trained (Brookman-Frazee, Drahota, et al, 2012).…”
Section: Barriers To Treating Co-occurring Asd and Mental Health Condition(s)mentioning
confidence: 99%